IMPROVING WATER EFFICIENCY IN HIGHER EDUCATION INSTITUTIONS: CONTRIBUTIONS FROM THE BOA VISTA CAMPUS OF THE FEDERAL INSTITUTE OF RORAIMA - Araújo, Hilton Brandão; Soares, Paulo Valladares [UNESP]; Espuny, Maximilian [UNESP]; de Oliveira, Otávio José [UNESP] (RGSA- Revista de Gestao Social e Ambiental, 2024)
Objective: The objective of this work is to propose recommendations to improve the management of water resources in a federal higher education institution, aiming to increase water use efficiency and promote a culture of sustainability among students and the local community. This can serve as a benchmark for institutions with similar characteristics. Theoretical Framework: Efficient management of water resources is crucial given the growing global challenge of water scarcity, especially in educational contexts, as they consume a lot of this resource and have a commitment to citizen education. The theoretical framework includes concepts related to sustainability, resource management, and educational institution practices. Method: The methodology adopted for this research comprises a single case study, which allowed for an in-depth analysis of institutional practices and their environmental impacts. Data collection was carried out through various methods, including document analysis, interviews with key stakeholders, and observations of water use practices. Results and Discussion: The results highlight the identification of good practices and challenges faced in water resource management within the institution. The discussion contextualizes these results in light of the theoretical framework, highlighting the implications for sustainability and efficiency in water use. Areas of inefficiency were identified, and sustainable strategies were developed. Possible discrepancies and limitations of the study are also considered in this section. Research Implications: The practical and theoretical implications of this research provide insights into how the results can be applied or influence practices in the field of sustainable water management in educational environments. These implications include recommendations for short, medium, and long-term actions that are replicable to other institutions. Originality/Value: This study contributes to the literature by updating sustainable water management practices in educational environments and offers significant applied contributions to the implementation of effective water management solutions. The relevance and value of this research are evidenced by its potential impact on decision-making by managers of other educational units.
MEJORANDO LA EFICIENCIA HÍDRICA EN INSTITUCIONES DE EDUCACIÓN SUPERIOR: CONTRIBUCIONES DEL CAMPUS BOA VISTA DEL INSTITUTO FEDERAL DE RORAIMA
MELHORANDO A EFICIÊNCIA HÍDRICA EM INSTITUIÇÕES DE ENSINO SUPERIOR: CONTRIBUIÇÕES DO CAMPUS BOA VISTA DO INSTITUTO FEDERAL DE RORAIMA
Keywords: Case Study; Efficient Water Use; Environmental Impact; Higher Education; Sustainability; Water Resource Management